Students' Perceptions of the Javanese English Accents through Extensive Listening Video - Syahri, Indawan; Sulaiman, Masagus; Azhari, Abi Musa (CV. Doki Course and Training, 2024)
This research aimed at figuring out the students’ perceptions on the Javanese English accents through extensive listening video and also identifying the challenges occurred within the process of listening to the Javanese English accents both in extensive listening and interactive speaking classes. This research employed a qualitative research design in line with a case study. The participants of this research were the fourth semester students of English Department of STKIP PGRI Lubuk Linggau who took extensive listening and interactive speaking classes. To collect the data, the researchers used a documentation technique in term of giving questionnaires. To analyze the data, the researchers used a percentage analysis. The results showed that most of students had positive perceptions on the Javanese English accent. They perceived that understanding various kinds of English accents could give them many advantages in their learning process and the challenges and difficulties that students identified in listening to the Javanese English accent did not make all of them have a negative perception. In conclusion, understanding various kinds of English accents could give them many advantages in learning English.